The Development of An Adjustable Low-pass Filter for A Partial Discharge Detection System under Testing with The Power Frequency Converter - Leelachariyakul, Banyat; Yutthagowith, Peerawut (My University, 2019)
In this paper presents the partial discharge detection system based on the power frequency converter as a low-voltage source and an adjustable low-pass filter which is constructed from variable inductor and fixed capacitor. The inductance is able to vary in the range of 8.69 mH to 18.82 mH. This adjustable low-pass filter circuit in partial discharge detection system is able to filter the undesired harmonic voltage and also reduce background noise. It is compatible with partial discharge detection system for high voltage equipment. The background noise of the commercial partial discharge detection system and the total harmonic distortion (THDv) of the testing voltage are improved. The results show that this low-pass filter that had been designed and constructed is capable for filtering the noise from a power frequency converter in the PD test and the undesired harmonic voltage sufficiently. The quality of the testing high voltage is good and sufficient for testing equipment such as potential transformers. Thus, application of this particular adjustable low-pass filter with variable cut-off frequency to the power frequency converter is a promising approach for generation of an AC sinusoidal voltage for the partial discharge detection system.
Keywords: adjustable low-pass filter; background noise; high-voltage tests; partial discharge; power frequency converter; total harmonic distortion; variable inductor